PENGARUH KUALITAS LAYANAN, PERSEPSI NILAI, CUSTOMER EXPERIENCE TERHADAP KEPUASAN PELANGGAN SATE KLATHAK PAK PONG - Indriati, Ari; Fitriana, Nita (Puslitabmas Batam Tourism Polytecnic, 2022)
This study aimed to determine the effect of Service Quality, Perceived Value, and Customer Experience on Customer Satisfaction at Sate Klathak Pak Pong Restaurant in Bantul. The population was customers who have purchased at the Sate Klathak Pak Pong Restaurant, Bantul. The sample in was 80 respondents. The sampling technique used purposive sampling method. The data was collected by distributing questionnaires. The data analysis used multiple linear regression analysis, hypothesis testing using the F test, T-test, and the coefficient of determination test. The results of this study indicated that service quality and perceived value had a significant positive effect on customer satisfaction. Meanwhile, customer experience did not have a significant effect on customer satisfaction.